Protein Extraction From Seeds as a Strategy for Valorizing Agroindustrial Subproducts and Wastes: Challenges, Techniques, and Scaling-up Potential - Marques, Bianca C.; Maniglia, Bianca C.; Favaro-Trindade, Carmen S.; Luchese, Claudia L.; Fai, Ana Elizabeth Cavalcante; Martelli-Tosi, Milena; Polachini, Tiago C. [UNESP]; Pinho, Samantha C. (Springer Nature, 2025)
A significant amount of the subproducts and residues generated in industrial fruit processing comprises seeds, which are often underutilized as a source of nutrients and are usually considered waste, fuel, or destined for animal feed. As the global demand for nonanimal proteins increases, grains and legume seeds have become important sources because of their high protein content. However, fruit seeds, a less traditional alternative, are gaining increasing attention as a viable source of protein with significant potential for nutritional and industrial applications. This review analyzes the composition and structural characteristics of seeds that are either traditionally used as food or are regarded as residues, considering their potential to cause chemical or physical interference in protein extraction. Various techniques, both established and emerging, developed to overcome these drawbacks are presented and discussed. These techniques include ultrasound-assisted, microwave-assisted, and high-pressure-assisted extractions, as well as high-voltage electrical treatments. This review focuses on the advantages, yields, operating parameters and limitations, and environmental impacts, as well as the influences of individual extraction processes on the structure and techno-functional properties of protein ingredients. The possibilities of scaling up these extraction methods are addressed, highlighting current limitations and recent examples from the literature. Extensive efforts are still needed to produce seed proteins at the industrial scale, but a laboratory-scale basis for these advances has been established, particularly with the support of novel environmentally friendly extraction techniques.